Atomic resolution analysis of a 2:1 complex of CpG and acridine orange. - Wang, A H (1979)
Cytidylyl-3', 5'-guanosine and acridine orange crystallize in a highly-ordered triclinic lattice which diffracts X-rays to 0.85 angstrom resolution. The crystal structure has been solved and refined to a residual factor of 9.5%. The two dinucleoside phosphate molecules form an antiparallel double helix with the acridine orange intercalated between them. The two base pairs of the double helical fragment have a twist angle of 10 degrees and it is found to have a C3' endo-(3', 5')-C2' endo mixed sugar puckering along the nucleotide backbone as has been observed for other simple intercalator complexes. Twenty-five water molecules have been located in the lattice together with a sodium ion. The intercalator double helical fragments form sheets which are held together by van der Waals interactions in one direction and hydrogen bonding interactions in the other. The crystal lattice contains aqueous channels in which sixteen water molecules are hydrogen bonded to the nucleotide, none to the intercalator, five water molecules are coordinated about the sodium ion and four water molecules bind solely to other water molecules. The bases in the base pairs have a dihedral angle of 7 to 8 degrees between them.